Soil and Ground Factors Affecting the Steel Underground Pipelines Corrosion Process and their Computer Simulation - V. N. Romaniuk; A. M. Niyakovskii; N. V. Strutsky; A. L. Svistun (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
Corrosion of various gas pipelines,especially such widespreadtype of it aselectrochemical ones,isthemainthreattosteelundergroundpipelines during the operational phase. The negativeeffect of corrosionisthedirectloss of metal,increasedmaterialandlaborcostsformaintenance,repairandreplacement of pipelines,equipmentdowntime,deterioration of safetyandenvironmentalsituationincase of release of the pumpedproduct(especiallyifit is combustiblegasoroilandpetroleum products)into the environment.Thearticleprovides an analysis of the complex of soil-and-soilfactorsaffectingtheintensity of corrosionprocessesoccurringonundergroundsteelpipelines, and highlightscurrentresearchapproachestothisissue as well asdomesticandforeign relevant literature sources. Thekeyparametersdetermining the corrosiveaggressiveness of the soil,suchashumidity,soil aeration,its physical-and-mechanical properties, the chemicalcomposition of the soilelectrolyte(including the content of chloridesandsulfates), the presence of a number of specificsoilmicroorganisms, areconsidered. The possibility and expediency of using the computer simulation method to assess their impact using modern software tools, in particular, the SOLID and ANSYS software environments, as well as neural network modeling technologies, are considered and demonstrated. Computer simulation provides ample opportunities for analyzing and predicting corrosion processes depending on changes in environmental conditions, which can be of great practical importance for a better understanding of these processes and their impact on the reliability and durability of steel underground pipelines inthesespecificconditions.